A Polydopamine-Functionalized Carbon Microfibrous Scaffold Accelerates the Development of Neural Stem Cells - Yang, Yanru; Zhang, Yuhua; Chai, Renjie; Gu, Zhongze (Frontiers in Bioengineering and Biotechnology, 2020)
Neuroregenerative medicine has witnessed impressive technological breakthroughs in recent years, but the currently available scaffold materials still have limitations regarding the development of effective treatment strategies for neurological diseases. Electrically conductive micropatterned materials have gained popularity in recent years due to their significant effects on neural stem cell fate. Polydopamine (PDA) -modified materials can also enhance the differentiation of neurons. In this work, we show that PDA-modified carbon microfiber skeleton composites have the appropriate conductivity, three-dimensional structure, and microenvironment regulation that are crucial for the growth of neural stem cells. The design we present is low-cost and easy to make and shows great promise for studying the growth and development of mouse neural stem cells. Our results show that the PDA-mediated formation of electrically conductive and viscous nanofiber webs promoted the adhesion, organization, and intercellular coupling of neural stem cells relative to the control group. PDA induced massive proliferation of neural stem cells and promoted the expression of Ki-67. Together, our results suggest that the composite material can be used as a multifunctional neural scaffold for clinical treatment and in vitro research by improving the structure, conductivity, and mechanical integrity of the regenerated tissues.